Visual solutions as a resource to promote mathematical learning - Vale, Isabel (2018)
Seeing is an important component in mathematical understanding, that can be developed, learned and taught. It is important to teach students how to see what is necessary, proposing challenging and adequate tasks. The use of visual solutions can be an alternative to the use of concepts that the student may not have learnt, and an easier way to solve a given situation. Therefore, the mathematics class should include practices and resources that lead students to think visually from experiences that imply this type of thinking. We intend to discuss some of these ideas and present examples of tasks, with multiple solutions, developed in the scope of a teacher training course.